2019
DOI: 10.1371/journal.pone.0215326
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease and pregnancy complications among Sri Lankan women: A cross sectional analytical study

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) is the commonest cause of liver disease worldwide and is the hepatic manifestation of metabolic syndrome. Effects of NAFLD on pregnancy is still unclear with few studies showing an association to gestational diabetes and pre-eclampsia. We aimed to describe the association between the NAFLD and pregnancy complications. This is the first study, to our knowledge, in a South Asian population. Method A cross sectional anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
2
15
0
1
Order By: Relevance
“…This study indicates that prevalence of fatty liver among pregnant women in Anuradhapura, Sri Lanka is much higher than the reported values from HICs and the previously reported in the South Asian context. Strengthening the evidence generated elsewhere 34,35 this prospective study indicate that NAFLD, specifically Fatty liver Grade II? Correct?…”
Section: Table 2: Comparison Of Liver Parameters Plasma Glucose and Biophysical Measurements By Fatty Liver Grades Among 632 First Trimessupporting
confidence: 52%
“…This study indicates that prevalence of fatty liver among pregnant women in Anuradhapura, Sri Lanka is much higher than the reported values from HICs and the previously reported in the South Asian context. Strengthening the evidence generated elsewhere 34,35 this prospective study indicate that NAFLD, specifically Fatty liver Grade II? Correct?…”
Section: Table 2: Comparison Of Liver Parameters Plasma Glucose and Biophysical Measurements By Fatty Liver Grades Among 632 First Trimessupporting
confidence: 52%
“…( 210 ) Fatty liver based on US findings has been associated with higher likelihood of gestational diabetes mellitus (GDM), independent of BMI and age. ( 211‐213 ) A population‐based cohort study also reported higher rates of cesarean delivery (64.2% vs. 16.8%), preterm births (16.4% vs. 5.1%), and small for gestational age births (5.8% vs. 2.8%) ( 214 ) in patients with NAFLD compared with non‐NAFLD controls, even after adjustment for BMI and pre‐GDM. ( 214 ) However, NAFLD was only associated with increased risk in women with BMI less than 30 kg/m 2 at conception.…”
Section: Management Of Chronic Liver Diseases During Pregnancy and Lamentioning
confidence: 97%
“…The search included an assessment of unpublished literature. All the studies included focused on NAFLD during a pregnancy [10][11][12][13][14][15][16][17], NAFLD as an associated outcome in pregnancy; often to GDM [5-7 & 25-28] or evaluated NAFLD in women assessing for co-variates such as hormonal and lifestyle factors [18][19][20][21][22][23][24]. Pregnancy related outcomes were only extracted from the first two groups.…”
Section: Study Protocolmentioning
confidence: 99%